Investigation of Edible Mushrooms As A Gastronomic Product: The Case of Ermenek (Karaman) - ŞİMŞEK, Aykut; ÇELİK YEŞİL, Seher (Journal of Hospitality and Tourism Issues, 2023)
Mushrooms were initially discovered by trial and error, and today their edibility has been scientifically found and taken their place on the table. The diversity of fungi also shows itself in the geography of Turkey. In this study it is aimed to determine what the edible mushrooms grown in Ermenek are, in which months they are collected, how these mushrooms are consumed and stored, how they are obtained, how to understand whether they are poisonous, what are the reasons for consumption, and to record the recipe of a dish made with these mushrooms. In line with the research, semi-structured interview technique with snowball sampling method was used, and data were collected from 15 participants by conducting online interviews on 24-30 October 2021. It has been determined that seven types of mushrooms are grown in total. These mushrooms are truffle mushrooms, Gold Flecked Woodwax, oyster mushroom, black morel, the white-footed elf cup, cultivated mushrooms, and morchella dunalii. Currently, these mushrooms collected in the region are generally used in food areas and in health areas and sold on a small scale. In addition, it was determined that they gathered mushrooms according to trial and error method, habit status, and traditional methods.
Keywords: 2. Zero hunger